Reconceptualizing the Public Spaces of New Urban Areas in Hanoi: The End or the New of Public-Making? - Tran, Minh Tung; Phan, Tien Hau; Chu, Ngoc Huyen (International Journal of Sustainable Construction Engineering and Technology, 2021)
Public spaces are designed and managed in many different ways. In Hanoi, after the Doi moi policy in 1986, the transfer of the public spaces creation at the neighborhood-level to the private sector has prospered nature of public and added a large amount of public space for the city, directly impacting on citizen’s daily life, creating a new trend, new concept of public spaces. This article looks forward to understanding the public spaces-making and operating in KDTMs (Khu Do Thi Moi - new urban areas) in Hanoi to answer the question of whether â€˜socializationâ€™/privatization of these public spaces will put an end to the urban public or the new means of public-making trend. Based on the comparison and literature review of studies in the world on public spaces privatization with domestic studies to see the differences in the Vietnamese context leading to differences in definitions and roles and the concept of public spaces in KDTMs of Hanoi. Through adducing and analyzing practical cases, the article also mentions the trends, the issues, the ways and the technologies of public-making and public-spaces-making in KDTMs of Hanoi. Win/loss and the relationship of the three most important influential actors in this process (municipality, KDTM owners, inhabitants/citizens) is also considered to reconceptualize the public spaces of KDTMs in Hanoi.